Seeking the unseen: Localization and surgery for an occult sporadic insulinoma - Subasinghe, D; Gunatilake, S. S. C.; Dassanayake, V. E.; Gunasinghe, C.; Ganewaththa, E.; Appuhamy, C.; Somasundaram, N. P.; Sivaganesh, S. (Korean Association of Hepato-Biliary-Pancreatic Surgery, 2020)
Insulinomas are rare pancreatic neuroendocrine tumours and the commonest cause for endogenous hyperinsulinaemic hypoglycemia. Small tumours are not easily detected by conventional cross-sectional imaging making localization prior to surgical removal a challenge. Selective arterial calcium stimulation is an invaluable adjunct to localization in such circumstances. This is further supplemented by intraoperative ultrasonography. A 39-year-old male was referred with features of Whipple's triad of 10 months duration. Clinical and biochemical evaluation including C-peptide and serum insulin levels during supervised hypoglycemia concluded endogenous hyperinsulinaemia as the underlying aetiology. Contrast CT and MRI of the abdomen failed to localize the tumour. Selective arterial calcium stimulation localized the lesion in distal pancreas. During the surgery, tumour was further localized to the tail of the pancreas using intraoperative ultrasonography and enucleated. Histology confirmed an insulinoma and patient made an unremarkable recovery and was well more than a year after the surgery.
Ann Hepatobiliary Pancreatic Surgery: 2020 May 31;24(2):234-238.
Keywords: Insulinoma; Selective arterial calcium stimulation; Enucleation